Association of eruption timing of first permanent molars and incisors with body mass index of children in Bengaluru City - Priya Subramaniam; Raksha Pagadala (Wolters Kluwer Medknow Publications, 2020)
Background: Tooth eruption is influenced by various factors which include physiological and genetic factors. The first permanent teeth to erupt are the permanent first molars at the age of 6 years. The timing of eruption of permanent teeth can be affected by the body mass index (BMI) which is a predictor of the overall growth of the child. Aim: The aim of the study was to determine the association of eruption timing of the mandibular and maxillary first permanent molars and incisors with BMI of children in Bengaluru city. Materials and Methods: In this cross-sectional study, 3166 schoolchildren (1636 boys and 1530 girls) between the ages of 5 and 10 years were selected. Oral examination was carried out to record the presence of the permanent first molars and incisors. The height in meters and weight in kilograms of each child were recorded and the BMI was calculated. Statistical Package for Social Sciences for Windows, Version 22.0, Released 2013, IBM Corp., Armonk, NY, USA, was used to analyze the data. The median age of eruption was calculated by using Probit analysis. Independent sample Student's t-test was used to compare the distribution of erupted teeth between girls and boys at different age groups. The association between BMI and eruption timing was derived using Pearson's correlation coefficient. Results: The first permanent tooth to erupt was the mandibular first molar at the age of 5.76 ± 1.3 years. Girls showed an earlier age of eruption of all the teeth except the mandibular central incisors. A statistically significant inverse association was seen between BMI and eruption timing of the teeth examined (P < 0.05). Conclusion: The median eruption timing of the mandibular permanent first molar and incisors was earlier than that of the maxillary counterparts. Children with higher BMI values showed earlier eruption timing of the permanent teeth examined.